Variability And Hetrosis In Green Fruited Brinjal - Sathya Varma PC (Department Of Olericulture, College Of Horticulture, 1995)
The present investigation on “Variability and heterosis in green fruited brinjal (Solanum melongena L.)”was conducted at the Vegetable Research Farm, College of Horticulture, Thrissur during 1992 – 94. Twenty three genotypes of brinjal collected from different parts of the country were grown in a randomised block design with two replications to assess the extent of genetic variability for fifteen characters viz., plant height, plant spread, number of primary branches per plant, days to first flowering, number of flowers per cluster, days to first fruit set, days to first harvest, average fruit weight, total fruits per plant, percentage of productive flowers, fruiting period and fruit yield per plant. The genotypic and phenotypic coefficients of variation, heritability, genetic advance and genetic gain were estimated. Correlation studies and path coefficient analysis were conducted to study the association among yield and its component characters and to estimate the direct and indirect effects of component characters on yield. Based on genetic divergence the 23 genotypes were grouped into five clusters. Seven superior genotypes were selected from these clusters based on their field performance and bacterial wilt resistance. The seven genotypes were crossed in a 7 x 7 diallel pattern to get 21 F1 hybrides. These F1 hybrids were evaluated along with their parents to derive information on general and specific combining ability and heterosis. Significant variation was observed among the genotypes for all the 12 characters studied, indicating scope for improvement. High heritability along with high genetic advance was observed for the characters fruit yield per plant, total fruits per plant, average fruit weight and percentage of productive flowers, indicating the action of additive genes. From the correlation studies, it was observed that yield had positive significant correlation with total fruits per plant, fruiting period, average fruit weight and number of flowers per cluster and negative significant correlation with days to first flowering, fruit set and harvest. Path coefficient analysis revealed that the character total fruits per plant had the maximum direct effect on yield. From the combining ability analysis it was noticed that the parental lines SM 247, SM 246 and SM 6 – 6 were good combiners for yield. The best combination for yield was SM 246 x SM 262 and that for earliness was SM 6 – 6 x SM 141. Significant heterosis was observed in many of the hybrids for most of the characters. SM 141 x SM 262 was the hybrid showing significant positive heterosis for plant height, plant spread, number of primary branches, average fruit weight and fruit yield per plant. Similarly SM 6 – 6 x SM 141 was the earliest hybrid to flower, set fruits and be harvested. This also showed the lowest percentage of bacterial wilt incidence. Another hybrid which showed significant heterosis for total fruits per plant, fruit yield and percentage of wilt incidence was SM 6 – 6 x SM 197. The study of heterosis thus revealed that the three hybrids viz., SM 141 x SM 262, SM 6 – 6 x SM 141 and SM 6 – 6 x SM 197 are promising combinations showing superiority in most of the economic characters considered for the study.